"Statistical analysis and forecasting of business activity in the regions of the Republic of Uzbekistan" (Multidisciplinary Journal of Science and Technology, 2024)
The article evaluates the activities of small businesses and private entrepreneurship in the innovative development of regions and predicts them on the basis of multiple options. The impact of the CPPTS on GDP by regions is analyzed. As a result of these analyzes, conclusions were drawn on improving the innovative environment of the regions.